Drivers of participation in Facebook long-term care groups: Applying the use and gratification theory, social identification theory, and the modulating role of group diversity. (March 2020) - Lin, Tung-Cheng; Fang, David; Hsueh, Siang-Ying; Lai, Ming-Cheng
Facebook long-term care groups have been established by long-term care workers, and few studies have explored the related drivers of participation from the perspective of caregivers. This study applied a mixed-methods approach; the qualitative component conducted a pilot study to explore the drivers of participation in Facebook long-term care groups and found that the use and gratification theory provides a valid approach for explaining these drivers. Subsequently, the quantitative component, based on the use and gratification theory, proposed a conceptual model to examine the effect of these drivers on the social identity of these groups as well as the modulating effects of extraversion and group diversity in terms of age and educational background. The results showed that the most important social identification–related driver underlying participation in these groups was self-discovery. In addition, the relationship among these drivers and social identification was found to be modulated by extraversion, age, and educational background.